Recurrent massive pulmonary emboli in a critically ill patient with COVID-19 - Aaron, L; Welch, M; Shah, A; Thomas, T; McKechnie, SR (Wiley, 2020)
We report the haematological management of a critically ill patient with coronavirus disease 2019 (COVID-19), with recurrent massive pulmonary emboli. A previous healthy 56-year-old man presented to the emergency department with severe hypoxaemic respiratory failure due to suspected COVID-19. He required invasive mechanical ventilation and transfer to the intensive care unit for increasing ventilatory requirements and cardiovascular instability. A computed tomography (CT) pulmonary angiogram demonstrated large bilateral pulmonary emboli with right heart strain, for which he received intravenous systemic thrombolysis followed by therapeutic weight-adjusted anticoagulation with low molecular weight heparin (dalteparin). Two weeks later, following an acute respiratory deterioration, a repeat CT pulmonary angiogram demonstrated a new saddle embolus with right heart strain requiring another regime of intravenous systemic thrombolysis. This occurred despite anti-Xa-guided therapeutic anticoagulation. The dose of therapeutic dalteparin was increased incrementally to an eventual dose of 12,500 units twice daily. A low threshold for radiological imaging should be considered in all COVID-19 patients with acute cardiorespiratory deterioration. Multidisciplinary team discussions highlighted aspects of balancing the risks of bleeding from anticoagulation vs. risk of death from pulmonary embolism. This report highlights the need for further research into the underlying mechanisms and optimal management of thrombotic complications in COVID-19.